A poética da metáfora em Hiroshima, mon amour - Lisboa, Silvia Maria de Pina Santos (2023)
This dissertation has as main object of investigation the poetics of metaphor in the film “Hiroshima mon amour”, directed by Alain Resnais from a screenplay by Marguerite Duras and released in 1959. Metaphor is a figure of speech widely used in various artistic manifestations; it is present, transcending the domain of aesthetics and providing new interpretations, thus making the artistic object timeless. From considerations bequeathed by philosophical and literary studies, from Aristotle (2020) to Paul Ricoeur (2015) and Maurice Blanchot (2018), we intend to verify the use of metaphor by modern cinema, based on theories by Marcel Martin (2013), Christian Metz (1980) and Deleuze (2007), going through a specific survey of the state of the art produced around the film. While metaphor recognizes the logical structure of language, it transgresses it; in cinematographic language it is the image that constitutes the base element and it is through it that the metaphor will manifest itself. In a film, even if the verbal language is present through the dialogues, it is the image that will prevail; it speaks to us without necessarily having to resort to the spoken or written word, the whole meaning is transposed into the image. This is the operation that will be verified in the narrative development of “Hiroshima mon amour”, a film that continues to raise questions and studies even after more than 60 years of its release, both for its aesthetics and for the subjective questions regarding the human that it can raise, much of it materializing through the metaphorical relationships present in it. In this sense, the present research focuses more on the authorship of Marguerite Duras, as we perceive that the metaphor is presentin a more marked way in her entire work than in the filmography of Alain Resnais. In “Hiroshima” we have a script that presents itself with its literary marks, despite this, it is necessary to understand how the images, through the use of metaphor, allow us to visualize a relationship between the film and other languages.